Pengaruh Literasi Laporan Keuangan dan Wawasan Kewirausahaan pada Penggunaan Informasi Akuntansi di Era Digitalisasi: - Kamilah K.; Jukhairia Ritonga; Annisa Zahra; Dela Pratama; Rizqia Humaira Nasution (LPPM Institut Nasional Laa Roiba Bogor, 2023)
Financial statement literacy is a form of someone's understanding of the financial condition of an institution with the aim of making decisions. Financial statements must be prepared in accordance with applicable PSAK and must be relevant, accurate, reliable, credible and easy to understand. The purpose of this study was to determine the effect of financial statement literacy and entrepreneurial insight on the use of accounting information in the digitalization era. The population in this study were MSME actors in Petangguhan Village, Galang District, Deli Serdang Regency with a sample of 50 MSME actors. In this study, researchers used quantitative methods. Where the data obtained in the form of numerical data or numbers that can be measured with certainty. Furthermore, the results of these observations were analyzed. The variables in this study consisted of independent variables, namely financial statement literacy, entrepreneurial insight, and subjective norms, and one dependent variable, namely the influence of financial statement literacy and entrepreneurial insight on the use of accounting information in the digitalization era. And the data obtained from the distribution of questionnaires given to MSME actors in Petangguhan Village. And respondents' answers were processed using the SPSS 26 application Keywords: Financial Report Literacy, Entrepreneurial Insights, Accounting Information